Poetry Collection Development Kit for School Libraries - [Unknown] (Knowledge quest, 2014)
Louisiana State <http://lsupress.org/books/by-subject/ poetry>, Pittsburgh (samples for some books in Pitt Poetry Series <www. upress.pitt.edu/renderHtmlPage. aspx?srcHtml=htmlSourceFiles/Series/ poetry.htm>, including Blanco's Looking for the Gulf Motel), and Yale (Yale Younger Poets Series) <http://yalepress. yale.edu/yupbooks/youngerpoets.asp> Free Online Resources Poets and Poems * Academy of American Poets <www. poets.org> includes an interactive U.S. poetry map <www.poets.org/page.php/ prmlD/382>; an app <www.poets.org/ page.php/prmlD/404> for the site is also available * From the Fishouse <www.fishousepoems. org> offers an audio archive of emerging poets; it also supports keyword searching * PennSound <www.writing.upenn.edu/ pennsound> features an audio archive featuring a wide range of poets * Poetry 180 <www.loc.gov/poetry/180/ pi 80-list.html> offers a poem-a-day project edited by Billy Collins * Poetry Daily <http://poems.com> offers poems reprinted with poet bio and stay on the site for one year; an app <http:// poems.com/special_features/app/ app_announce.php> is also available for the site * Poetry Out Loud <www.poetryoutloud. org> offers an annual high school competition, as well as some audio files * Poetry Tool (Poetry Foundation) <www. poetryfoundation.org> supports subject browsing; it offers podcasts and an app <www.poetryfoundation.org/mobile> * Verse Daily offers poems reprinted with poet bio and links to other poems by the poet * Writer's Almanac <http://writersalmanac. publicradio.org> offers audio text archive for the popular public radio program Poetic Craft: * How a Poem Happens <http:// howapoemhappens.blogspot.com> offers poems and interviews with poets (e.g., Spera's "In a Field Outside the Town") * Learning Lab (Poetry Foundation) <www. poetryfoundation.org/learning/> * On Writing (American Academy of Poets) <www.poets.org/page.php/prmlD/55> Multimedia Poetry (two examples from tbe Pulitzer Center for Crisis Reporting): * Hope: Living and Loving with HIV in Jamaica <www.livehopelove.com> features poems by Kwame Dawes * Voices from Haiti <http://pulitzercenter. org/features/voices-haiti> features poems by Kwame Dawes Online Literary Magazines: For help selecting from the thousands of literary magazines available, including many online (e.g., Cortland Review <www.cortlandreview.com>), consult the NewPages Guide to Literary Magazines, 2013 <www.newpages.com/LitMagPDF>.